Paremiologia na warsztacie leksykografa. W stronę słownika przyjaznego odbiorcy - Szutkowski, Tomasz (Studia Rossica Posnaniensia, 2017)
The paper features a treatment of the basic postulates that are aimed at developing a proverb dictionary, which would, on the one hand, characterize the assembled material in an optimal and comprehensive way, and retain the status of a user-friendly dictionary, on the other hand. This “friendliness” is achieved through the simplification of formal description, the withdrawal of acronyms and references, and the reduction of redundant comments and explanations. The order of particular description elements is also of considerable importance in the process of developing a dictionary, which will, first and foremost, allow the user to easily acquire as broad a knowledge about proverbs as possible in an accessible and effective way.